Transformasi Pengajaran Bab Nikah dalam Kitab Fathul Qorib: Studi Implementasi di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Transformation of Teaching the Marriage Chapter in the Book of Fathul Qorib: Implementation Study at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Lia Febriani; Syafiq Otto Setiawan; Oktavia Syifa Rahmawati; Fadzli Rokhman (Litera Academica Publishing, 2025)
This study aims to examine how the transformation of teaching methods in the Marriage Chapter (Bab Nikah) of the Fathul Qarib book is implemented at Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The main objective of this research is to understand the forms of change, strategies, and impacts of the transformation of kitab kuning (classical Islamic text) teaching on students’ understanding, particularly in the context of fiqh al-munakahat (Islamic family law). This study employs a qualitative descriptive approach with a case study design. Data were collected through participant observation, in-depth interviews with the head of the boarding school, teachers, and students, as well as documentation of learning activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing based on the Miles and Huberman model. The results indicate that the transformation of teaching the Marriage Chapter involves innovations in teaching approaches, the use of more varied learning media, and the contextualization of material with contemporary social issues. Teaching no longer focuses solely on theoretical understanding and text memorization but also emphasizes practical application and the relevance of marriage law within Indonesia’s social context. This transformation allows Fathul Qarib teaching to maintain its classical scholarly essence while becoming more applicable and responsive to modern challenges.This research is expected to contribute to the development of kitab kuning teaching methods in Islamic boarding schools and serve as a reference for implementing contextual, interactive, and relevant teaching strategies in Islamic jurisprudence education.